2006
DOI: 10.1245/s10434-006-9146-1
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Colorectal Cancer with Un-Resectable Liver Metastases: Immediate Colorectal Resection or Up-Front Systemic Chemotherapy?

Abstract: The rate of complications related to the non-resected colorectal tumor is very low using oxaliplatin as first line chemotherapy. Non-operative management of asymptomatic colorectal cancers with un-resectable liver metastases is a safe approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(106 citation statements)
references
References 24 publications
1
90
0
11
Order By: Relevance
“…By contrast, in Western countries, a number of reports have shown that treatment often commences with drug therapy using FOLFOX/ FOLFIRI + molecularly targeted drugs, followed by resection of the primary cancer. The foci of metastasis are then treated with anticancer drugs followed by surgical resection where possible (9)(10)(11). Each of these therapeutic strategies has advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in Western countries, a number of reports have shown that treatment often commences with drug therapy using FOLFOX/ FOLFIRI + molecularly targeted drugs, followed by resection of the primary cancer. The foci of metastasis are then treated with anticancer drugs followed by surgical resection where possible (9)(10)(11). Each of these therapeutic strategies has advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…More than 100,000 new colon cancer cases were expected to be diagnosed in 2014, and about 20% of these cases are likely to have metastatic disease at presentation [1,2]. Unfortunately, only a small number of patients with stage IV disease can be cured with DRug EvaluatiOn Uboha & Hochster future science group multimodality therapy.…”
Section: Fluoropyrimidines and Colon Cancermentioning
confidence: 99%
“…De 1999 à 2006, 7 études comparant une chirurgie première à une chimiothérapie première chez des patients avec un cancer colorectal métastatique ont été publiées : 5 études rétrospec-tives, une étude cas-témoins et une étude prospective [37][38][39][40][41][42][43]. Les résultats de ces différentes études ont été analysés dans une revue de la littérature publiée en 2008 [19].…”
Section: Chimiothérapie Premièreunclassified
“…En fonction des études, la survie globale variait de 14 à 23 mois en cas de chirurgie première et de 8,2 à 22 mois en cas de chimiothérapie première (Ta bleau 1). Dans 4 des 6 études, aucune différence significative n'est retrouvée entre les deux options thérapeutiques premières [37][38][39][40][41]. Dans 2 des 6 études, il existe une différence statistiquement significative en faveur d'une chirurgie première mais les patients des deux groupes n'étaient pas comparables et les patients traités par chimiothérapie première étaient en moins bon état général et/ou avaient une extension métastatique plus importante que les patients traités par chirurgie première [42,43].…”
Section: Chimiothérapie Premièreunclassified